Characterization of Biochar Derived from Durian Shells by Pyrolysis Process - Thonglem, Sutatip; Intawin, Pratthana (Research on Modern science and Utilizing Technological Innovation Journal (RMUTI Journal), 2020)
The objective of this research was to study the properties of durian shells biochars prepared by the pyrolysis process. The durian shells were contained in a closed chamber and heated in an electric furnace at different temperatures which varied from 500 oC to 900 oC for 10 hours. After heating, durian shells turned into black color. Density and porosity, surface morphology, elemental compositions, and crystalline phases of biochars were investigated by Archimedes immersion technique, scanning electron microscope (SEM), Energy dispersive x-ray spectrometry (EDX) and X-ray diffractometer (XRD), respectively. An increase in pyrolysis temperature led to yield reduction and an increase in the bulk density of biochars. SEM analysis showed the distribution of pore on all biochars fractures with similar apparent porosity values of more than 70%. The main elements in all biochars contained carbon (C) and oxygen (O), which were studied by EDX analysis. XRD results showed phase formation of carbon in biochar, which could form both amorphous and semi-crystalline phases. While oxygen could be composed in other elements in biomass through many forms of mineralogical compositions as CaCO3 (Calcite), KHCO3 (kalicinite), and Ca3(PO4)2. Moreover, the alkali lignin phase appears in biochar at 500 oC and 600 oC conditions because of a highly cross-linked structure of the lignin. The CaCO3 and Ca3(PO4)2 phases could decompose at low pyrolysis temperature, but KHCO3 phase formed at high temperatures hence the thermal stability of the KHCO3 phase was higher than CaCO3 and Ca3(PO4)2 phases.